Dynamics of spatial phase coherence in a dissipative Bose–Hubbard atomic system - Vatré, Rémy; Bouganne, Raphaël; Bosch Aguilera, Manel; Ghermaoui, Alexis; Beugnon, Jérôme; Lopes, Raphael; Gerbier, Fabrice (Comptes Rendus. Physique, 2024)
We investigate the loss of spatial coherence of one-dimensional bosonic gases in optical lattices illuminated by a near-resonant excitation laser. Because the atoms recoil in a random direction after each spontaneous emission, the atomic momentum distribution progressively broadens. Equivalently, the spatial correlation function (the Fourier-conjugate quantity of the momentum distribution) progressively narrows down as more photons are scattered. Here we measure the correlation function of the matter field for fixed distances corresponding to nearest-neighbor (n-n) and next-nearest-neighbor (n-n-n) sites of the optical lattice as a function of time, hereafter called n-n and n-n-n correlators. For strongly interacting lattice gases, we find that the n-n correlator $C_1$ decays as a power-law at long times, $C_1\propto 1/t^{α }$, in stark contrast with the exponential decay expected for independent particles. The power-law decay reflects a non-trivial dissipative many-body dynamics, where interactions change drastically the interplay between fluorescence destroying spatial coherence, and coherent tunnelling between neighboring sites restoring spatial coherence at short distances. The observed decay exponent $α ≈ 0.54(6) $ is in good agreement with the prediction $α =1/2$ from a dissipative Bose–Hubbard model accounting for the fluorescence-induced decoherence. Furthermore, we find that the n-n correlator $C_1$ controls the n-n-n correlator $C_2$ through the relation $C_2 ≈ C_1^2$, also in accordance with the dissipative Bose–Hubbard model.